A 32-Year-Old Female with AIDS, Pneumocystis jiroveci Pneumonia, and Methemoglobinemia - Guillermo J. Giangreco; Dean Campbell; Mark J. Cowan (Case Reports in Critical Care)
We report a case of methemoglobinemia with significant hemoglobin desaturation in a young female with AIDS who was being treated for Pneumocystis jiroveci pneumonia. A review of the etiology, pathophysiology, and treatment of methemoglobinemia is presented.